Literature of Waste Management (Sorting Of Organic And Inorganic Waste) Through Digital Media In Community - Indah Nur Chazanah; Asep Bayu Dani Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2022)
This study aims to educate the public regarding good and correct waste management, both in terms of definitions, interests and procedures for good and correct waste management using digital literacy methods in the community. Education was carried out to 21 community members in Cimahi City, Indonesia, using digital literacy methods in the form of providing information and learning through digital media to explain related subjects taken. The information provided to the public is made as attractive as possible using an attractive design. The education process is carried out online (providing information and discussions through WhatsApp groups) and offline (through direct socialization to the public). Community understanding was analyzed through pretest and posttest questions as many as 20 questions. The results showed that there was an increase in the results of the pretest submitted to the posttest at the end of the activity. Education is done successfully and the public can understand. This shows that educational activities are successful because the information conveyed is interesting and raises public interest in understanding information and applying it in everyday life. This research provides information that infographics and videos can be used as educational media. In addition, an attractive design can generate public interest in understanding the information conveyed. This shows that educational activities are successful because the information conveyed is interesting and raises public interest in understanding information and applying it in everyday life. This research provides information that infographics and videos can be used as educational media. In addition, an attractive design can generate public interest in understanding the information conveyed. This shows that educational activities are successful because the information conveyed is interesting and raises public interest in understanding information and applying it in everyday life. This research provides information that infographics and videos can be used as educational media. In addition, an attractive design can generate public interest in understanding the information conveyed